Підхід до автоматичної побудови функцій інтерпретації під час навчання онтологій - Литвин, В. В.; Хрущ, С. Б. (My University, 2014)
Розглянуто підхід до автоматизованої побудови функцій інтерпретації (аксіом) концептів та відношень онтологій предметної області під час її навчання. Розроблено метод розпізнавання семантики природномовних текстів та її подання у вигляді описової логіки. In the paper the approach to automated construction of interpretation functions (axioms) of concepts and relations of the domain ontology during its training are considered. The method of recognizing the semantics of natural language texts and its representation in the form of descriptive logic.
The approach to automatic building of functions interpretation during learning ontologies
Keywords: онтологія; навчання онтологій; інтелектуальна система; база знань; функції інтерпретації; описова логіка; ontology; learning ontologies; intelligent system; knowledge base; interpretation; descriptive logic